Fiscal and Academic Efficiency Index of the Public School Districts of Arkansas - Mary F. Hughes (Educational Considerations, 2004)
In Lake View v. Huckabee, the Supreme Court of Arkansas stated that the Education Article of the Arkansas Constitution designates the state, rather than the General Assembly, as the entity to maintain a general, suitable, and efficient system of free public schools.